2016
DOI: 10.1002/cmdc.201600121
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Drug Images and Repurposing Drugs with BioGPS and FLAPdock: The Thymidylate Synthase Case

Abstract: Repurposing and repositioning drugs has become a frequently pursued and successful strategy in the current era, as new chemical entities are increasingly difficult to find and get approved. Herein we report an integrated BioGPS/FLAPdock pipeline for rapid and effective off-target identification and drug repurposing. Our method is based on the structural and chemical properties of protein binding sites, that is, the ligand image, encoded in the GRID molecular interaction fields (MIFs). Protein similarity is dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 92 publications
0
26
0
Order By: Relevance
“…In the present work, we designed and synthesized compounds 1 – 3 , analogues of 1A – 3A respectively, in order to compare the binding modes and the affinities of flavanones with those of flavonols. Compounds 1 – 3 were synthesized by condensation between substituted acetophenone and benzaldehydes in the presence of thionyl chloride in ethanol, as previously reported ( Scheme 1 ) [ 21 ]. The compounds were characterized by 1 H-NMR, 13 C-NMR and mass analysis and the data are reported in the Supporting Information (p. S2).…”
Section: Resultsmentioning
confidence: 99%
“…In the present work, we designed and synthesized compounds 1 – 3 , analogues of 1A – 3A respectively, in order to compare the binding modes and the affinities of flavanones with those of flavonols. Compounds 1 – 3 were synthesized by condensation between substituted acetophenone and benzaldehydes in the presence of thionyl chloride in ethanol, as previously reported ( Scheme 1 ) [ 21 ]. The compounds were characterized by 1 H-NMR, 13 C-NMR and mass analysis and the data are reported in the Supporting Information (p. S2).…”
Section: Resultsmentioning
confidence: 99%
“…Compared with other flavonoids, apigenin can selectively induce cell cycle arrest and apoptosis of cancer cells with low mutagenicity and toxicity against normal cells and thus is gaining attention as a promising anticancer adjuvant [ [8] , [9] , [10] ]. Moreover, the structure and chemical properties of its protein binding site suggests that apigenin can inhibit the catalytic TS reaction by hydrogen bonding to the pyrimidine carbonyl and hydroxyl groups of deoxyribose dUMP [ 11 ]. Furthermore, several studies have suggested potential therapeutic efficacy in CRC cells, but it is still unclear whether apigenin can improve 5-FU sensitivity and regulate TS expression in CRC cells.…”
Section: Introductionmentioning
confidence: 99%
“…This threshold was tuned while we were developing BioGPS, five years ago. Thereafter, we’ve tested it in other datasets, proving its validity to capture polypharmacology [15, 21]. Reassuringly, when analyzing co-crystallized ligands in the PDB, we observed that pairs of pockets above this cutoff indeed tend to accommodate the same ligands (S1A–S1C Fig), being cavities able to embed the totality of the ligand (S1D Fig) while remaining relatively small (S1E Fig) and highly specific for ligand-binding regions (>40% of the cavities overlap with ligands).…”
Section: Resultsmentioning
confidence: 99%
“…A systematic way to detect pairs of proteins that could share a ligand is to compare binding sites in their 3D structures [14, 15]. Arguably, the design of ligands that dock to similar pockets is simpler and more suited to the current medicinal chemistry toolbox, and binding site characterization and comparison methods have flourished with this aim [16].…”
Section: Introductionmentioning
confidence: 99%